L2 Efficacy and safety outcomes with odevixibat in children with progressive familial intrahepatic cholestasis due to deficiencies in multidrug resistance protein 3 (PFIC type 3) or myosin 5B (PFIC type 6). (12th September 2022) - Özen, Hasan; Sokal, Etienne; Lacaille, Florence; Dalgic, Buket; Ni, Quanhong; Kjems, Lise; Horn, Patrick
Abstract : Introduction/Background: Progressive familial intrahepatic cholestasis (PFIC) is a group of rare, inherited liver diseases. Initial descriptions of PFIC were primarily based on data from patients with PFIC type 1 (PFIC1) or 2 (PFIC2). However, additional forms of PFIC have been identified. The ongoing, phase 3 PEDFIC 2 study is assessing the effects of odevixibat, an ileal bile acid transporter inhibitor, in patients with any type of PFIC. Aim: As of a data cut-off date of 4 December 2020, 6 patients with PFIC types other than PFIC1 or PFIC2 had enrolled in PEDFIC 2. Here, we describe efficacy and safety outcomes in this subset of patients, which comprises 5 patients with PFIC type 3 (PFIC3) and 1 with PFIC type 6 (PFIC6). Subjects and Methods: In PEDFIC 2, all patients receive open-label odevixibat 120 μg/kg/day. Assessments include change from baseline in serum bile acids (sBAs), pruritus, hepatic biochemical parameters, growth, and sleep. Patient pruritus and sleep were evaluated twice daily by caregivers using the validated PRUCISION scale. Pruritus responses range from 0 to 4, with higher scores indicating worse symptoms. Other outcomes included proportion with sBA response (ie, sBAs reduced ≥70% or levels ≤70 μmol/L), proportion of positive pruritus assessments (PPAs) at the patient level (ie, pruritus score ≤1 or a ≥1-point drop from baseline), and treatment-emergent adverse events (TEAEs). Results: Patients with PFIC3 ranged in age from 3.7–13.3 years, and the 1 patient with PFIC6 was 12.8 years old at screening. All 6 patients were ongoing in the study at the data cut-off. Mean (range) exposure was 41 (34−54) weeks for the 5 PFIC3 patients and 54 weeks for the 1 PFIC6 patient. From baseline to last assessment, all patients had reductions in sBAs and all but 1 patient (PFIC3) had reductions in pruritus score. Mean changes from baseline to week 36 in sBAs, pruritus score, growth, sleep parameters, and liver parameters are shown in the table 1 . Three patients, including 2 with PFIC3 and 1 with PFIC6, met criteria for sBA response at last assessment. Over the interval from weeks 0–36, PPAs in 5 patients with available data were ≥85%. Overall, 5 of 6 patients experienced any TEAE; no patients had serious TEAEs or TEAEs leading to discontinuation. Keywords: progressive familial intrahepatic cholestasis, clinical trial, odevixibat, ileal bile acid transporter inhibitor, pruritus, bile acids Topic: General gastroenterology, general hepatology Conflict of Interest Declaration H. Özen and B. Dalgic: Nothing to disclose E. Sokal: Promethera Biosciences – Founder, chairman of the board of directors, and member of the executive committee F. Lacaille: Alexion – Consultant Q. Ni, L. Kjems, P. Horn: Albireo – Current or former employment This study was sponsored by Albireo. Medical writing and editorial assistance were provided by Peloton Advantage, LLC, an OPEN Health company, and were funded by Albireo Pharma, Inc. Summary and Conclusion: Patients with PFIC3 or PFIC6 experienced clinical benefits with odevixibat, including reductions in sBAs and improvement in pruritus symptoms, growth, and sleep parameters. Odevixibat treatment was generally well tolerated.